(untitled) (Research, Society and Development, 2026)
This study aimed to implement a quality indicator in the routine of physiotherapy internships in a hospital ward, with a view to systematizing and monitoring care practices. It is an observational, cross-sectional study with a descriptive approach and an applied implementation component, conducted at the São João Batista Hospital in Viçosa (MG), with tenth-semester physiotherapy students. The indicator was applied daily during a 24-day internship cycle, after prior training of the participants, and the data were analyzed descriptively, considering adherence, completion, and feasibility of the instrument. The results show high adherence to the use of the indicator, with application on 100% of the days of care, in addition to adequate completion in most records. The instrument proved to be easy to apply, with reduced completion time and no negative interference in the care routine. However, the study identifies doubts related to conceptual standardization, the scope of variables, and the absence of guidelines for specific situations, indicating the need for structural adjustments. It is concluded that the implementation of the indicator is feasible and well-accepted in the context of the hospital internship, contributing to the organization, systematization, and monitoring of physiotherapy practices, although refinements are needed to improve its applicability and accuracy in future studies.